2020
DOI: 10.7189/jogh.10.010413
|View full text |Cite
|
Sign up to set email alerts
|

Surviving mothers and lost babies – burden of stillbirths and neonatal deaths among women with maternal near miss in eastern Ethiopia: a prospective cohort study

Abstract: Background Although maternal near miss (MNM) is often considered a 'great save' because the woman survived life-threatening complications, these complications may have resulted in loss of a child or severe neonatal morbidity. The objective of this study was to assess proportion of perinatal mortality (stillbirths and early neonatal deaths) in a cohort of women with MNM in eastern Ethiopia. In addition, we compared perinatal outcomes among women who fulfilled the World Health Organization (WHO) and the sub-Saha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
4
12
2
3
Order By: Relevance
“…In support of the current study, there existed an association between MNM and higher rates of adverse perinatal outcome born to these mothers [45,57,65,66]. Tura et al claim that adverse perinatal outcomes among MNM women is self-evident given the fact that MNM are identi ed using severe clinical criteria along with organ disfunction, which was also supported by their ndings [28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In support of the current study, there existed an association between MNM and higher rates of adverse perinatal outcome born to these mothers [45,57,65,66]. Tura et al claim that adverse perinatal outcomes among MNM women is self-evident given the fact that MNM are identi ed using severe clinical criteria along with organ disfunction, which was also supported by their ndings [28].…”
Section: Discussionsupporting
confidence: 82%
“…Studies from southern and northern Ethiopia reported that multiparity was a risk factor for NNM [26,27]. A recent prospective cohort study in Ethiopia reported that grand multiparity was a risk factor for perinatal mortality among women with MNM [28].…”
Section: Discussionmentioning
confidence: 99%
“…In support of the current study, an association between MNM and higher rates of adverse perinatal outcome was found (47,54,61,62). Tura et al claim that adverse perinatal outcomes among SAMM women is self-evident given the fact that SAMM are identi ed using severe clinical criteria along with organ disfunction (30).…”
Section: Discussionsupporting
confidence: 79%
“…A recent prospective cohort study in Ethiopia reported that grand multiparity was a risk factor for perinatal mortality among women with MNM (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that complications leading to MNM also contribute to adverse perinatal outcomes, the magnitude and causes of perinatal deaths among women with MNM are mainly unknown in low- and middle-income countries. The stillbirth rate among women with WHO-MNM in Suriname (193/1000 births) is higher than reported in Brazil (140/1000 births) [ 37 ] or other Latin American countries (128/1000 births) [ 30 ], and lower than in low-resource settings (eg, Ethiopia 284/1000 births [ 38 ]). The higher stillbirth rate among women with WHO-criteria (than Namibian- or SSA-criteria) further confirms that the WHO-tool comprises of the most clinically severe criteria.…”
Section: Discussionmentioning
confidence: 90%